TEACHER INTEREST IN TEACHING AMONG SCHOOL TEACHER’S IN THE CONTEXT OF AREA, TYPE OF SCHOOL AND GENDER - Joshi, Megha P; Prajapati, A. N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A teacher’s teaching interest in student learning is the basic pillar of education. Hence, the present research has been undertaken. The purpose of this study is to examine teachers’ interest in teaching in the context of area, type of school, and gender. This research was an ex-post-factor type of research. A purposive sampling method was used to select 80 teachers in Dahod district. The collection of data was carried out with the help of Kakkar’s Interest in Teaching Value Scale. The data was analyzed using the ’t’ test. The findings of the present study show that there is no significant difference in the terms of teachers’ interest in teaching by area, gender, and type of school.